PREDICTD PaRallel Epigenomics Data Imputation with Cloud-based Tensor Decomposition - Timothy J. Durham (Nature Portfolio, 2018)
Assays to characterize the epigenome and interrogate chromatin state genome wide have so far been performed in a selected set of conditions. Here, Durham et al. develop a computational method based on tensor decomposition to impute missing experiments in collections of epigenomics experiments.